Analisis Lanskap Kota Bersejarah Parakan dengan Pendekatan Historic Urban Landscape (Hul) - Setiawan, Athaya Mazaya Rifa; Waluyo, Totti; Liddan, Arkananta (CV. Gio Architect, 2025)
Parakan, as one of the historical areas in Indonesia, has a rich culture that is reflected in the city landscape and architectural heritage. This research aims to analyze historical elements in Parakan through the Historic Urban Landscape (HUL) approach which integrates physical, social and cultural aspects in city landscape management. The research methodology includes field observations to understand the actual conditions of the area and literature review to identify relevant HUL principles. The research results show that HUL's approach is able to reveal the potential and challenges in preserving the historic Parakan area, including modernization pressures and conservation needs. The conclusion of this research emphasizes the need for synergy between cultural heritage preservation and sustainable city development to maintain Parakan's historical identity.